Adsorptive removal of COD from produced water using tea waste biochar - Khurshid, Hifsa; Ul Mustafa, Muhammad Raza; Rashid, Umer; Isa, Mohamed Hasnain; Yeek, Chia Ho; Muhammad Shah, Mumtaz (Elsevier, 2021)
This study was conducted to explore the effectiveness of tea waste (TW) biochar (BC) as an adsorbent for the oxidizable organic contaminants measured as chemical oxygen demand (COD) in produced water (PW). BCs were prepared by modifying the TW with single (pre-pyrolysis) and combined (pre and post pyrolysis) treatments using phosphoric acid and hydrogen peroxide solutions. Based on FTIR, XPS, XRD and BET characterizations, the combined modified BC had higher oxygen-containing functional groups (-OH and -COOH), surface area (82 ± 0.50 m2/g) and pore volume (0.08 ± 0.001 cm 3/g) compared to single modified BC (60 ± 0.50 m2/g, 0.02 ± 0.002 cm 3/g). The Langmuir monolayer adsorption model best fitted both BCs with separation factor < 1, showing favorable adsorption process. The controlling mechanism of the adsorption process was best described by the pseudo-second-order kinetic model with a coefficient of determination value of 0.995. The particle diffusion mechanism was demonstrated by the Weber–Morris plot. Taguchi method was used in Minitab 19 for optimization of operating factors i.e., pH, contact time and BC dosage. Maximum COD removal efficiencies were found to be 89.35 ± 0.5% and 95.5 ± 0.5% for single and combined modified BCs, respectively. The study provides a successful approach towards high level of COD removal from PW while reducing the waste generation and protecting the environment.